Brazilian immigrant fathers' perspectives on child's eating and feeding practices: a qualitative study conducted in the United States. Issue 17 (24th December 2020) - Lindsay, Ana Cristina; Vianna, Gabriela Vasconcellos de Barros; Arruda, Carlos André Moura; Alves, Amanda De Sá Melo; Hasselmann, Maria Helena; Machado, Márcia MT; Greaney, Mary L
Abstract: Objectives: Brazilians comprise a rapidly growing immigrant Latino group in the USA, yet little research has focused on health issues affecting Brazilian children in immigrant families. As increasing evidence is documenting fathers' influential role in their children's eating behaviours and ultimately weight status, the current study sought to explore the Brazilian immigrant fathers' perspectives and practices related to child's feeding practices and their preschool-aged children's eating. Design: Qualitative study using in-depth, semi-structured interviews. Interviews were conducted in Portuguese by native Brazilian research staff using a semi-structured interview guide. Interviews were audio-recorded and transcribed verbatim. Transcripts were analysed thematically using a hybrid approach that incorporated deductive and inductive analytical approaches. Setting: Massachusetts. Participants: Twenty-one Brazilian immigrant fathers who had at least one child aged 2–5 years. Results: Results revealed fathers' awareness of the importance of healthy eating for their children, their influence as role models and their involvement in feeding routines of their preschool-aged children. Moreover, fathers were receptive to participating in family interventions to promote their children's healthy eating. Nearly all fathers reported wanting to learn more and to do 'what's right' for their children. Conclusions: The current study provides new information about Brazilian immigrant fathers' views about factors influencing their children's healthy eating behaviours and paternal feeding practices. Future research should quantify fathers' feeding styles and practices and solicit fathers' input in the design of culturally appropriate family interventions targeting the home environment of preschool-aged children of Brazilian immigrant families.